The role of social media advertisements as an independent variable in the final consumer’s purchase decision, which is the dependent variable, from a sample viewpoint of the faculty members at the colleges of Salahuddin University- Erbil. - اىٍػرس اىٍفاغػ ٌطٍػ ضفَ عيیفّ (QALAAI ZANIST SCIENTIFIC JOURNAL, 2018)
This research aims to analyze the role of social media advertisements as an independent variable in the final consumer’s purchase decision, which is the dependent variable, from a sample viewpoint of the faculty members at the colleges of Salahuddin University- Erbil. Through trying to identify the extent of follow-up members of the research sample of social media advertisements, as well as to see how the research sample influenced by social media advertisements. According to their characteristics by asking some questions, which focused on the impact and the nature of the relationship between the research variables, and embodied this role in the model of research and hypotheses emanating from them, then subjected to a set of statistical tests. Moreover, this research used a descriptive, analytical method to reach the research aims. Further, the researcher prepared a questionnaire to obtain a complete and accurate perception of the subject of the research and distributed to the lecturers within the colleges of Salahaddin University-Erbil. Moreover, the sample number is (350) individuals. However, the hypotheses tested by using the statistical program (SPSS V.22). So, the researcher reached a set of results, the most important is the existence of the relationship and impact between social media advertisements and the final consumer purchase decision, and based on the findings of the researcher provided some suggestions and recommendations.